Dukungan Informasi bagi Ibu-ibu Menyusui dalam Memberikan ASI Eksklusif di Kecamatan Gondokusuman Kota Yogyakarta (KEMAS: Jurnal Kesehatan Masyarakat, 2016)
AbstractBreast milk is the first and the best choice of food for infants in early life. Various efforts have been taken by the government of Indonesia to encourage mothers to breastfeed their children exclusively. However, exclusive breastfeeding outcomes in most areas are still low. Yogyakarta is one of those areas, especially in the Gondokusuman Subdistrict with breastfeeding outcome only 23.2%. The outcome should be 80% according to the target in the Minimum Service Standards of Health. The succes of 23.2% breastfeeding mothers to breast feed exclusevely because of the support that receive by them, one is the informational support.The purpose of this study was to determine what kind of informational support to breast feed exclusively which is received by nursing mothers in the Gondokusuman Subdistrict. The type of research is qualitative with a phenomenological approach. In depth interviews and focus group discussion (FGD) are used for data collection techniques. Depth interviews were conducted to mothers who exclusively breastfed, mothers who did not exclusively breastfeed, the husband of nursing mothers, and health care workers. Investigation of the trustworthiness of the study using triangulation of methods and sources. Thematic Content Analysis is used for data analysis. These results indicate that informational support is very important for pregnant and nursing mothers to be able to provide exclusive breastfeeding to their babies. Informational support in the form of support from health workers and significant others, the support of health care and UKBM (Community Based Health Unit), availability of health promotion media, completeness of information, easier access of information for nursing mothers. Information gleaned from significant others or people who are influential for nursing mothers have a more important role, because of the closer emotional factor. Therefore, nursing mothers need to build a positive environment in order to obtain sufficient information for the success of exclusive breastfeeding.Keyword : Exclusive breastfeeding, Informational support, Phenomenological